Genome-wide association study of pulpal and apical diseases - Salminen, Aino; Hyvärinen, Kati; Ritari, Jarmo; Leppilahti, Jussi M.; Palotie, Ulla; Vuollo, Ville; Kambur, Oleg; Reis, Kadri; Reigo, Anu; Palta, Priit; Perola, Markus; Sinisalo, Juha; et al. (Nature communications, 2025)
Infections of the dental pulp are common sequelae of microbial activity and host susceptibility, affecting >80% of adult population. We performed a genome-wide association study on endodontic infections utilizing Finnish health registry and genotype data from FinnGen. Cases [132,124 (27.2%)] had at least one ICD10-diagnosis code of pulpal or apical diseases, whereas 353,106 individuals without diagnoses served as controls. We investigated two clinical sub-phenotypes, Pulpitis and Necrosis of pulp or apical periodontitis. Our analysis resulted in significant associations in 12 chromosomes and 15 independent loci, such as those near HORMAD2 gene and those in the HLA region. The imputed HLA alleles, especially DRB1 * 04:01 and DQB1 * 03:01, were associated with endodontic infections. Bioinformatic analysis of the top variants indicated several potential regulatory variants which are involved in MHC class II protein complex, humoral immune responses, and antigen processing. Our study widens understanding on how immune dysregulation resulting from immunogenetic variation is involved in the pathogenesis of endodontic infections. Here the authors aim to further increase our understanding of host genetic variants predisposition to endodontic infections and perform a GWAS on FinnGen participants with diagnosis codes of pulpal and apical diseases derived from Finnish national health registers.